2020
DOI: 10.3390/catal10121444
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Ammonia Carriers for SCR Systems Using MOFs [M2(adc)2(dabco)] (M = Co, Ni, Cu, Zn)

Abstract: Ammonia is one of the most common reductants for the automotive selective catalytic reduction (SCR) system owing to its high NO2 reduction (deNOx) efficiency. However, ammonia carriers for the SCR system have sluggishly evolved to achieve rapid ammonia dosing. In this study, the MOFs [M2(adc)2(dabco)] (M = Co, Ni, Cu, Zn) were synthesized and characterized as ammonia carriers. Among the four obtained MOFs, Ni2(adc)2(dabco) possessed the highest surface area, 772 m2/g, highest ammonia uptake capacity, 12.1 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the rapid kinetics of the physisorption of ammonia has been reported before with a temperature swing adsorption (TSA) method, where it took a relatively long time to reach the decomposition temperature for the AEMHs ammines. 34,51,52 In our previous study, the zeolite X demonstrated 50% higher ammonia release in the first 10 min at low temperature (35 °C), suggesting the physisorbents can offer a rapid ammonia dosing in SCR at a lower temperature compared to the chemisorbents of AEMHs. 53 The TSA measurement results show that zeolite X releases 4 times higher ammonia (0.69 mmol g −1 ) than SrCl 2 (0.14 mmol g −1 ) in the first 10 min before reaching 60 °C (Section S5, ESI†).…”
Section: Resultsmentioning
confidence: 86%
“…However, the rapid kinetics of the physisorption of ammonia has been reported before with a temperature swing adsorption (TSA) method, where it took a relatively long time to reach the decomposition temperature for the AEMHs ammines. 34,51,52 In our previous study, the zeolite X demonstrated 50% higher ammonia release in the first 10 min at low temperature (35 °C), suggesting the physisorbents can offer a rapid ammonia dosing in SCR at a lower temperature compared to the chemisorbents of AEMHs. 53 The TSA measurement results show that zeolite X releases 4 times higher ammonia (0.69 mmol g −1 ) than SrCl 2 (0.14 mmol g −1 ) in the first 10 min before reaching 60 °C (Section S5, ESI†).…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, during the ammonia desorption at low temperature (35 °C), the NaX scaffold released 40% ammonia uptake (approximately 3.5 mmol g -1 ) in the first 10 min, which was 50% higher than the MgCl2 of 4% (approximately 2.3 mmol g -1 ). The rapid kinetics in the NaX scaffold in the low-temperature regime is due to the physisorption mechanism, where NaX scaffold possesses BET surface area of 335 m 2 g -1 , much higher than 3 m 2 g -1 of the MgCl2 [13,21]. In the designed unit, the NaX scaffold can start to offer the ammonia dosing at low temperature to minimize the buffering time, and once the cartridge reaches the decomposition temperature of Mg(NH3)6Cl2 at 135 °C, the MgCl2 can contribute the most ammonia dosing with its superior ammonia capacity.…”
Section: Ammonia Sorption Characterizationmentioning
confidence: 99%
“…Recently, Cao et al reported the structured SrCl 2 , SrCl 2 /graphite, SrCl 2 /rGO, and MOF composites using the freeze-casting method. Those composites showed good efficiency concerning NH 3 uptake and sorption kinetics [ 12 , 14 , 15 ]. However, extraordinary volume changes are expected during NH 3 sorption for typical structures and composites of AEMHs.…”
Section: Introductionmentioning
confidence: 99%